Ensuring Data Integrity Scheme Based on Digital Signature and Iris Features in Cloud - Salah H. Abbdal; Thair A. Kadhim; Zaid Ameen Abduljabbar; Zaid Alaa Hussien; Ali A. Yassin; Mohammed Abdulridha Hussain; Salam Waley (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Cloud computing is a novel paradigm that allows users to remotely access their data through web- based tools and applications. Later, the users do not have the ability to monitor or arrange their data. In this case, many security challenges have been raised. One of these challenges is data integrity. Contentiously, the user cannot access his data directly and he could not know whether his data is modified or not. Therefore, the cloud service provider should provide efficient ways for the user to ascertain whether the integrity of his data is protected or compromised. In this paper, we focus on the problem of ensuring the integrity of data stored in the cloud. Additionally, we propose a method which combines biometric and cryptography techniques in a cost-effective manner for data owners to gain trust in the cloud. We present efficient and secure integrity based on the iris feature extraction and digital signature.  Iris recognition has become a new, emergent approach to individual identification in the last decade. It is one of the most accurate identity verification systems. This technique gives the cloud user more confidence in detecting any block that has been changed. Additionally, our proposed scheme employs user’s iris features to secure and integrate data in a manner difficult for any internal or external unauthorized entity to take or compromise it. Iris recognition is an internal organ that is well protected against damage and wear by a highly transparent and sensitive membrane. Extensive security and performance analysis show that our proposed scheme is highly efficient and provably secure.